Determining correlations between the grade of lens opacity and tear levels of total antioxidant activity and lipid peroxidation products in patients having both cataract and bacterial keratitis - V. Ia. Usov; Abou Tarboush; S. G. Kolomiichuk (Journal of Ophthalmology)
Purpose: To determine correlations between the grade of lens opacity and tear levels of total antioxidant activity (TAA) and lipid peroxidation (LPO) products in patients having both cataract and bacterial keratitis treated versus not treated with methyl-ethyl pyridinol hydrochloride (MH).